Smart Cities (IntechOpen, 2026)
Smart Cities – Designing the Future of Urban Living presents a scholarly synthesis of modern smart urbanism, promoting a coherent, standards-compliant lexicon for digital public infrastructure, AI governance, and human-centered design. The volume connects theory and practice by turning normative frameworks such as equity, resilience, sustainability, and democratic legitimacy into practical advice on interoperability, outcome-based metrics, algorithmic transparency, rights-preserving security, energy systems transition, and circular economy practices. Readers will find helpful tools, such as governance patterns and procurement agreements, indicators and assessment rubrics, and finance concepts that turn pilots into long-lasting public value. Some of its unique strengths are its ability to compare different urban settings, its focus on multi-level governance and institutional capacity, and its insistence that technological "smartness" be shown through measurable improvements in well-being, environmental performance, and public trust. Written for city leaders and planners, engineers and educators, researchers and policy professionals, the book shows how to turn ideas into actions that can be held accountable. It connects data architectures to service quality, participatory co-production to legitimacy, and open standards to learning and scalability. This book provides readers with a solid foundation for planning the future of city living through a short, authoritative, methodologically sound, policy-relevant, and implementation-ready roadmap.